1993
DOI: 10.1002/bjs.1800800643
|View full text |Cite
|
Sign up to set email alerts
|

Detection and enumeration of circulating tumour cells in colorectal cancer

Abstract: Immunocytochemistry was used in parallel with conventional cytology to detect circulating malignant epithelial cells in 42 patients undergoing resection for colorectal cancer. Preoperative peripheral and peroperative mesenteric venous blood samples were taken. Tumour cells were isolated on a density gradient and cytospins prepared. Slides were stained by conventional cytology (May-Grünwald-Giemsa) and by an indirect immunoperoxidase technique with the anticytokeratin antibody KG8.13. Using conventional cytolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
34
0
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 16 publications
2
34
0
4
Order By: Relevance
“…Two previous studies have reported on intraoperative sampling of effluent venous blood from colon and renal cancers, but neither determined whether surgery had any effect on the rate of cell shedding (Glaves et al, 1988;Leather et al, 1993). Preliminary results using a polymerase chain reaction (PCR) technique to detect circulating tumour cells were similar to our findings, although fewer patients were studied (Brown et al, 1994).…”
supporting
confidence: 80%
See 3 more Smart Citations
“…Two previous studies have reported on intraoperative sampling of effluent venous blood from colon and renal cancers, but neither determined whether surgery had any effect on the rate of cell shedding (Glaves et al, 1988;Leather et al, 1993). Preliminary results using a polymerase chain reaction (PCR) technique to detect circulating tumour cells were similar to our findings, although fewer patients were studied (Brown et al, 1994).…”
supporting
confidence: 80%
“…The importance of the extent of tumour cell shedding into the bloodstream, and the effects of this on cancer surgery have, by contrast, been neglected. The significance of these factors in determining outcome therefore remains unknown.Monoclonal antibodies against epithelial-restricted epitopes now permit reliable identification of small numbers of carcinoma cells among large numbers of cells of haemopoetic lineage in the bloodstream and bone marrow (Leather et al, 1993;Pantel et al, 1993 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Most current methods do not seem to be sensitive or specific enough to detect circulating cells in significant numbers of patients with carcinomas (15)(16)(17). Recently, a major advance in this area occurred with the advent of flow cytometry, which makes possible the detection of CTCs in a good balance of sensitivity and specificity.…”
mentioning
confidence: 99%